Role of 18F FDG PET in Differentiating Benign and Malignant Primary Bone Tumors (Bangladesh Journal of Nuclear Medicine, 2015)
18F FDG PET is useful in differentiating benign from many kinds of malignant tumors including bone tumors. Many reporters found significant difference of SUV (standardized uptake value) between benign and malignant primary bone tumors. However, some benign bone tumors specially histolytic and Giant cell containing lesions show high accumulation of FDG, which increases false positive rates in FDG-PET. So, consideration of histologic subtypes should be included in analysis of SUV at FDG PET of primary bone tumors. Furthermore, high accumulation of FDG in inflammatory lesions like chronic osteomyelitis and rheumatoid arthritis should also be considered. Dual time-point imaging and determination of retention index provide more help in the differentiation of malignant from benign tumors and is recommended for unclear bone lesions. To differentiate benign from malignant vertebral compression fractures PET showed slightly higher sensitivity over MRI and provide better specificity when both modalities are combined. PET provides opportunity of whole body screening to pick up new lesions and also guide FNAC in case of indeterminate results. DOI: http://dx.doi.org/10.3329/bjnm.v17i1.22495 Bangladesh J. Nuclear Med. 17(1): 75-83, January 2014